Clinical challenges associated with utility of neoadjuvant treatment in patients with pancreatic ductal adenocarcinoma. Issue 6 (June 2022) - Gray, Simon; de Liguori Carino, Nicola; Radhakrishna, Ganesh; Lamarca, Angela; Hubner, Richard A.; Valle, Juan W.; McNamara, Mairéad G.
Abstract: Pancreatic ductal adenocarcinoma (PDAC) is an increasingly common cancer with a persistently poor prognosis, and only approximately 20% of patients are clearly anatomically resectable at diagnosis. Historically, a paucity of effective therapy made it inappropriate to forego the traditional gold standard of upfront surgery in favour of neoadjuvant treatment; however, modern combination chemotherapy regimens have made neoadjuvant therapy increasingly viable. As its use has expanded, the rationale for neoadjuvant therapy has evolved from one of 'downstaging' to one of early treatment of micro-metastases and selection of patients with favourable tumour biology for resection. Defining resectability in PDAC is problematic; multiple differing definitions exist. Multidisciplinary input, both in initial assessment of resectability and in supervision of multimodality therapy, is therefore advised. European and North American guidelines recommend the use of neoadjuvant chemotherapy in borderline resectable (BR)-PDAC. Similar regimens may be applied in locally advanced (LA)-PDAC with the aim of improving potential access to curative-intent resection, but appropriate patient selection is key due to significant rates of recurrence after excision of LA disease. Upfront surgery and adjuvant chemotherapy remain standard-of-care in clearly resectable PDAC, but multiple trials evaluating the use of neoadjuvant therapy in this and other localised settings are ongoing.